Numerical Simulation of Bedrock Sagging Sinkholes in Strain-Softening Rock Induced by Embankment Construction - Zhen Zhang; Zhongda Chen (Advances in Civil Engineering)
A bedrock sagging sinkhole occurred in Jiangxi Province of China when constructing the Changli freeway above shallow karst caves. It was chosen as a case to investigate the failure mechanism and potential evolution. The in situ stress of the study area was measured and numerically reproduced. The Hoek–Brown strength parameters were obtained by laboratory tests. A strain-softening constitutive model was established according to the strain-softening behaviour exhibited by the specimens in the triaxial test. The stress-strain curves of the specimens were reproduced by numerical methods. Then, bedrock sagging sinkholes in strain-softening rock induced by embankment construction were simulated. The occurrence of the strain-softening zone and its transition to the residual zone were observed and classified into four stages. The stress paths of the four stages were analysed. Interestingly, in this case, the supports at both ends of the bedrock began to yield from the top and extended downward, while the midspan position began to yield from the bottom and extended upward, and the reasons for yielding were related to tension. Further analysis found that the failure mode was basically consistent with the size and direction of the bending moment. In fact, this failure mode was quite similar to a fixed supported beam. Then, the feasibility of calculating the stability of karst caves based on beam assumptions was discussed. Finally, potential evolution of the bedrock sagging sinkhole was discussed.